Pharmacological effects of traditional herbal plant garlic (Allium sativum): A review - Paudel, Keshab Raj (Journal of Kathmandu Medical College, 2015)
This study aimed to review the different pharmacological effects of garlic. Garlic, Allium sativum, is a herbal plant which has been used in different food preparations since long time. Many studies have shown that allicin is the main compound in garlic which is generated from alliin with the help of alliinase enzyme and is responsible for many pharmacological effects. Different studies have shown that garlic has pharmacological effects such as antihypertensive, antihypercholesterolaemic, antiplatelet, hypoglycaemic, cardioprotective, antimicrobial, antineoplastic, etc. However, studies in the literature havesome confl icting fi ndings and meta-analyses are also slightly different for different effects. Despite these fi ndings, most of the studies, including meta-analyses, have shown signifi cant antihypertensive and hypolipidaemic effects of garlic. Based on the data in the literature, regular dietary consumption of raw garlic, two to four grams, equivalent to one clove of garlic, or 600-900 mg garlic powder per day, if not contraindicated, may be effective for different benefi cialpharmacological effects.Journal of Kathmandu Medical CollegeVol. 3, No. 4, Oct.-Dec., 2014Page: 158-161